WALANT Hand and Upper Extremity Procedures Performed With Minor Field Sterility Are Associated With Low Infection Rates. Issue 2 (May 2022) - Avoricani, Alba; Dar, Qurratul-Ain; Levy, Kenneth H.; Kurtzman, Joey S.; Koehler, Steven M.
Background: The use of minor field sterility in hand/upper extremity cases has been shown to improve workflow efficiency while maintaining patient safety. As this finding has been limited to specific procedures, we investigated the safety of performing a wide array of hand/upper extremity procedures outside the main operating room using minimal field sterility with Wide-Awake Local Anaesthesia No Tourniquet (WALANT) anaesthesia by evaluating superficial and deep infection rates across a diverse series of cases. Methods: This study was a case series conducted between October 2017 and June 2020. Of all, 217 patients underwent hand/upper extremity procedures performed in a minor procedure room via WALANT technique with field sterility. Primary outcome measures include superficial and deep surgical site infections within 14 days post-surgery. Results: Of all, 217 patients were included in this study; 265 consecutive hand/upper extremity operations were performed by a single surgeon, with notable case diversity. The majority of patients (n = 215, 99.1%) did not report or present with signs of infection before or after their operation. We report 0% 14-day and 0.37% 30-day surgical site infection rates for such hand/upper extremity procedures performed in a minor procedure room with field sterility. Conclusion: Hand/upper extremity procedures performed via WALANT technique with field sterility in a minor procedure room are associated with low surgical site infection rates. These rates are comparable to surgical site infection rates for similar surgeries performed in main operating rooms with standard sterilization procedures. Thus, the implementation of this technique may allow for improved workflow efficiency and reduced waste, all while maintaining patient safety.